Combined Analysis of Myocardial Deformation and Oxygenation Detects Inducible Ischemia Unmasked by Breathing Maneuvers in Chronic Coronary Syndrome - Spicher, Barbara; Fischer, Kady; Zimmerli, Zoe A.; Yamaji, Kyohei; Ueki, Yasushi; Bertschinger, Carina N.; Jung, Bernd; Otsuka, Tatsuhiko; Bigler, Marius R.; Gräni, Christoph; von Tengg-Kobligk, Hendrik; Räber, Lorenz; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: In patients with chronic coronary syndromes, hyperventilation followed by apnea has been shown to unmask myocardium susceptible to inducible deoxygenation. The aim of this study was to assess whether such a provoked response is co-localized with myocardial dysfunction. Methods: A group of twenty-six CAD patients with a defined stenosis (quantitative coronary angiography >50%) underwent a cardiovascular magnetic resonance (CMR) exam prior to revascularization. Healthy volunteers older than 50 years served as controls (n=12). Participants hyperventilated for 60s followed by brief apnea. Oxygenation-sensitive images were analyzed for changes in myocardial oxygenation and strain. Results: In healthy subjects, hyperventilation resulted in global myocardial deoxygenation (-10.2±8.2%, p<0.001) and augmented peak circumferential systolic strain (-3.3±1.6%, p<0.001). At the end of apnea, myocardial signal intensity had increased (+9.1±5.3%, p<0.001) and strain had normalized to baseline. CAD patients had a similar global oxygenation response to hyperventilation (−5.8±9.6%, p=0.085) but showed no change in peak strain from their resting state (-1.3±1.6%), which was significantly attenuated in comparison the strain response observed in controls (p=0.008). With apnea, the CAD patients showed an attenuated global oxygenation response to apnea compared to controls (+2.7±6.2%, p<0.001). This was accompanied by a significant depression of peak strain (3.0±1.7%, p<0.001), which also differed from the control response (p=0.025). Regional analysis demonstrated that post-stenotic myocardium was most susceptible to de-oxygenation and systolic strain abnormalities during respiratory maneuvers. CMR measures at rest were unable to discriminate post-stenotic territory (p>0.05), yet this was significant for both myocardial oxygenation (area under the curve (AUC): 0.88, p>0.001) and peak strain (AUC: 0.73, p=0.023) measured with apnea. A combined analysis of myocardial oxygenation and peak strain resulted in an incrementally higher AUC of 0.91, p<0.001 than strain alone. Conclusion: In myocardium of patients with chronic coronary syndromes and primarily intermediate coronary stenoses, cine oxygenation-sensitive CMR can identify an impaired vascular and functional response to a vasoactive breathing maneuver stimulus indicative of inducible ischemia.